Guilt appeals in advertising: investigating the roles of inferences of manipulative intent and attitudes towards advertising - Lwin, Michael; Phau, Ian (School of Marketing, Curtin Business School, 2008)
Guilt appeal has always been studied as a unified construct, literature however identifies three classifications of guilt namely, anticipatory, reactive and existential guilt, and this has left limiting our understanding of guilt appeals in advertising. This appeal is increasingly important for advertisers, due to changes in the Australian demographics, family lifestyles and societal values. These alterations have led to higher prevalence of guilt appeals in luxury and symbolic brands which are previously unexplored. Based on the research gaps, a research framework is proposed to examine these untested relationships between attitude towards the ad, ad credibility, inferences of manipulative intent and guilt arousal. Potential contributions are also discussed.